Manajemen Asuhan Kebidanan Pada Nn. “A” dengan obesitas di SMA Negeri 10 Gowa Tahun 2025 - Afrianisa, Nurul; Firdayanti, Firdayanti; Saleha, Sitti; Alkautzar, Anieq Mumthi’ah; Wahyuningsih, Tri (Jurnal Midwifery, 2026)
Adolescence is also a transitional age from childhood to adulthood, where at that age many changes are felt by teenagers searching for their identity by following the current trends and lifestyles of the current era. In Indonesia, the prevalence of childhood obesity based on body mass index (BMI/U) and age ratio in children aged 5–12 years increased from 8.8% (Riskesdas, 2013) to 9.2% (Riskesdas, 2018). The prevalence of obesity and overweight among adolescents aged 16 to 18 years also increased from 1.6% to 4.0% and from 5.7% to 9.5%, respectively. Obesity in adolescents is caused by many factors: lack of physical activity, unbalanced diet, excessive intake of macronutrients, frequent consumption of fast food, a history of obesity in parents, and the habit of skipping breakfast.This research paper aims to carry out Midwifery Care Management for Adolescent Ms. "A" with obesity at State Senior High School 10 Gowa from May 5 to June 23, 2025 using Varney's 7-step midwifery care management approach and documentation of the SOAP form.The results obtained by the Adolescent Midwifery Care Management Ms. "A" with obesity, the client complained of difficulty in carrying out activities due to being overweight and also easily tired during activities, and had a habit of eating excessive portions and not exercising. After eight weeks of care, the physical condition was good, not easily tired, vital signs were within normal limits, and weight loss was seen as the client began to regulate food portions and exercise every day.Conclusion and case study of 7-step Varney and SOAP care management, namely from the first visit to the eighth visit there were no complications, and the weight of Ms. "A" decreased to 53 kg and BMI 22.1 kg/m2, there was no gap between theory and the case of Ms. "A".